Note from the Editors-in-Chief - Sing, Alexandra; Subramanyan, Vighnesh (Consilience, 2012)
Dear Reader, It is our pleasure to present you Issue 8 of Consilience: The Journal of Sustainable Development. This past year has been filled with many milestones for us, as we have launched new opportunities for readers to engage with Consilience. Our new iPad App is now available for download from iTunes here. We believe that this is a major step forward in making Consilience accessible to our readers across a range of media. We are also pleased to announce the launch of our upgraded website, which may be viewed at www.consiliencejournal.org. Changes include an expansion of our Briefings column, featuring short articles by undergraduate and graduate students at Columbia University and other institutions, as well as a more vibrant and engaging photo essay section. We strongly encourage our readers to engage with these new facets of our website and contribute to the continuing dialogue on sustainable development. Specifically in regards to this issue, we are proud to present our special feature on Urban Development, which occupies the first 70 pages of this issue. In an era where more than half the world’s 7 billion people live in cities, the challenges involved in creating livable, healthy cities are very pressing. However, the special feature, seeking to provide glimpses into the concerns of this field, is in no way a holistic treatment of every issue in this domain. Rather, we give readers a taste of the scope of pressing matters in this area, in the hope that they will be motivated to delve further into this in other issues of Consilience, as well as in other reputed publications. Our three photo essays concerning urban development capture the essence of this section, approaching the urban from different, yet complementary, perspectives. Simon Fique’s concern for the influence of urban planning and architecture on community building in the developed world, by his exploration of Santiago de Compostela in Spain, contrasts to the rather more gritty concerns of Leandro Lima, in his discussion of a program to introduce media education into the favelas of Brazil. Yet they, as well as Laura Penaranda Currie, in her photo essay on planning and construction in Havana, Cuba, recognize the importance of the habitat that we construct for ourselves in determining our development and fulfillment as human beings. In a time when it may appear that the thinking on urban development is haphazard and disconnected, in both the developed and developing worlds, these essays serve as a heartening reminder of the true human scale and impact of these issues. We are excited about the coming year and encourage you to continue interacting with Consilience through readership, submissions, and through our Briefings column. As always, we look forward to receiving your feedback and hope that our work will in some way inspire engagement with the issues trending across the discipline of sustainable development. If you have any questions or comments, please do not hesitate to contact us atcontact@consiliencejournal.org. Enjoy the issue! Alexandra Sing Editor-in-Chief, AY 2012-2013 Consilience: The Journal of Sustainable Development Vighnesh Subramanyan Editor-in-Chief, AY 2011-2012 Consilience: The Journal of Sustainable Development